Penerapan Konsep Moderasi Beragama Pada Fatwa MUI : Studi Kasus Fatwa DSN-MUI No 77 Tentang Jual Beli Emas Secara Tidak Tunai dan Fatwa MUI No 38 Tentang Hukum Wanita Menjadi Khatib dalam Shalat Jumat - Rizaludin, Rizaludin (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The recent rise of radicalism threatens the foundations of national unity. As a multicultural nation, Indonesia has become fertile ground for radicalism—often stemming from misconceptions about Islamic teachings—prompting the emergence of a religious moderation movement built on three pillars: justice (*‘adalah*), balance (*tawazun*), and tolerance (*tasamuh*). While previous studies have generally examined moderation from theoretical-textual perspectives or within the contexts of education and digital *da’wah* (religious outreach), there remains a gap in understanding how these pillars are concretely actualized within the texts and methodologies of MUI (Indonesian Ulema Council) fatwas. This study aims to identify and analyze the application of these three pillars of religious moderation in MUI fatwas, using DSN-MUI Fatwa No. 77 (on non-cash gold transactions) and MUI Fatwa No. 38 (on the ruling regarding women serving as *khatib*—sermon givers—during Friday prayers) as case studies. Employing a qualitative approach based on library research, the study analyzes primary data (MUI fatwa texts) and secondary data (classical and contemporary literature) through a descriptive-analytical method. The findings indicate that both fatwas consistently incorporate the pillars of justice, balance, and tolerance into their formulation processes. This research offers a theoretical contribution by providing a new analytical framework for interpreting religious fatwas through the lens of religious moderation, as well as a practical contribution to MUI and other fatwa-issuing bodies in strengthening the narrative of moderation as a tool to prevent radicalism in Indonesia.